A miR‐15a related polymorphism affects NSCLC prognosis via altering ERCC1 repair to platinum‐based chemotherapy. Issue 21 (30th September 2022) - Xue, Ping; Zhang, Guopei; Zhang, Hongchao; Cui, Su; Zhang, Liang; Yu, Tao; Xiao, Mingyang; Li, Liuli; Lu, Xiaobo
Abstract: Platinum‐based chemotherapy is regarded as a preferential curative‐intent option for non‐small cell lung cancer (NSCLC), while the acquired drug resistance has become a major obstacle that limits its clinical application. Since the repair efficiency of tumour cells to platinum‐DNA adducts plays a crucial role in chemotherapy resistance, we aimed to explore whether several meaningful polymorphisms of DNA repair genes were associated with the benefits of platinum‐based chemotherapy in NSCLC patients. Firstly, six single nucleotide polymorphisms (SNPs) located in the 3'untranslated region (3'UTR) of three DNA repair genes were detected in 246 NSCLC patients receiving platinum‐based chemotherapy and analysed the correlation of these candidate SNPs with the overall survival. Cox proportional hazard model showed that NSCLC patients carrying ERCC1 rs3212986 AA genotype had a shorter overall survival compared to those with CC. Mechanistically, we performed tumour chemosensitivity assay to observe the convincing linkage of rs3212986 polymorphism with ERCC1 expression and cisplatin sensitivity. The subsequent in vitro experiments identified that rs3212986 polymorphism altered the post‐transcriptional regulation of ERCC1 via affecting the binding of miR‐15a, and further changed the sensitivity to platinum analogue. It reminded that patients carrying ERCC1 rs3212986 CC homozygote were expected to respond better to platinum‐based chemotherapy due to a lower expression of ERCC1. Compared with previous studies, our current comprehensive study suggested that rs3212986, a 3'UTR polymorphism in ERCC1, might have clinical relevance in predicting the prognosis of NSCLC patients receiving platinum‐based chemotherapy.